ANALISIS PENYALURAN DAN PENDAYAGUNAAN DANA ZIS PADA PROGRAM EKONOMI DI DT PEDULI SUMUT - Indah Khuzaimah; Muhammad Arif (Jurnal Ekonomi dan Bisnis, 2024)
DT Peduli is a National Amil Zakat Institution. Zakat funds that have been collected are then distributed to eight asnaf consisting of the poor, needy, amil, converts, gharim, riqab, fisabilillah, and ibn sabil. And during this pandemic, zakat funds are focused on being distributed to people affected by Covid-19. DT Peduli North Sumatra allocates its entire zakat funds to assist mustahik. 80% of the collected zakat monies will be disbursed, while the remaining 20% will be reserved for the subsequent year, in accordance with the standard operating procedure of DT Peduli North Sumatra. The objective of this study is to determine the geographical distribution of the utilisation of DT Peduli in North Sumatra. This study employs a descriptive research design utilising a qualitative research methodology, as it involves the examination of data in the form of statements. Utilization in this case concerns the utilization of zakat, where zakat is distributing zakat funds to mustahiq Program Analysis and Utilization of Zakat, Infaq, and Sadaqah (Zis) at DT Peduli North Sumatra.